REVIEW ON MULTIPLEXING TECHNIQUES IN OPTICAL COMMUNICATION SYSTEMS - Ekta; Sharma, Vikrant; Kaur, Dalveer (European Scientific Journal, ESJ, 2015)
In this paper, we present an overview of different multiplexing techniques. We focus on TDM, FDM, WDM, DWDM and CWDM. Basically multiplexing is an important part of communication system in which large number of users send data at the same time through a single link. Multiplexing is widely used in communication systems due to its potential to increase the channel utilization or transmission capacity and decrease system costs.